The impact of serological testing implementation on tick-borne encephalitis detection in Poland - Joanna Zajkowska; Elżbieta Waluk; Renata Świerzbińska; Justyna Dunaj; Olga Zajkowska; Dominik Wawrzuta; Jolanta Niścigorska-Olsen; Marek Matukiewicz; Barbara Oczko-Grzesik; Daniel Veltze; Katarzyna Bernacka-Andrzejewska; Katarzyna Burchart-Adamczyk; et al. (PLoS ONE, 2025)
Introduction Tick-borne encephalitis virus (TBEV) infections remain underreported in Poland, leading to inadequate public awareness of the potential severity of the disease and its preventive measures. Aim This study aims to assess the incidence of tick-borne encephalitis (TBE) in non-endemic regions of Poland by analyzing serum or cerebrospinal fluid (CSF) samples from patients with neuroinfections of unknown origin. Materials and Methods In this study, 29 departments specializing in neuroinfections were involved. Hospitals were chosen from regions classified as non-endemic with limited TBE reporting. Patients treated between April 1, and December 31, who had neuroinfections of unknown origin, were enrolled. Their CSF or serum samples underwent serological diagnosis of TBE using the Virotech ELISA kit at the Immunoserology Laboratory of the Medical University of Białystok. In addition, we used questionnaires to collect clinical and epidemiological data from patients, Results Among 766 patients, 124 exhibited serum or CSF antibodies against TBEV. None of them were vaccinated against TBE. The highest positivity rates were observed in Małopolskie (31%), Świętokrzyskie (24%), and Dolnośląskie (22%) voivodeships. In contrast, the Kujawsko-Pomorskie (2%), Pomorskie (3%), and Zachodniopomorskie (7.5%) voivodeships showed the lowest ratios. All patients reported their place of residence as a potential source of infection, some also mentioning outdoor activities, travel, work, and unpasteurized dairy consumption. Conclusions This study reveals a notable incidence of TBE infections in patients with nonspecific neuroinfections residing in regions historically seen as non-endemic. These findings emphasize the need for improved reporting and educational initiatives to raise awareness of the risk of TBE.